Detection of Target ssDNA Using a Microfabricated Hall Magnetometer with Correlated Optical Readout. (13th February 2012) - Hira, Steven M.; Aledealat, Khaled; Chen, Kan-Sheng; Field, Mark; Sullivan, Gerard J.; Chase, P. Bryant; Xiong, Peng; von Molnár, Stephan; Strouse, Geoffrey F.
Abstract : Sensing biological agents at the genomic level, while enhancing the response time for biodetection over commonly used, optics-based techniques such as nucleic acid microarrays or enzyme-linked immunosorbent assays (ELISAs), is an important criterion for new biosensors. Here, we describe the successful detection of a 35-base, single-strand nucleic acid target by Hall-based magnetic transduction as a mimic for pathogenic DNA target detection. The detection platform has low background, large signal amplification following target binding and can discriminate a single, 350 nm superparamagnetic bead labeled with DNA. Detection of the target sequence was demonstrated at 364 pM (<2 target DNA strands per bead) target DNA in the presence of 36  μ M nontarget (noncomplementary) DNA (<10 ppm target DNA) using optical microscopy detection on a GaAs Hall mimic. The use of Hall magnetometers as magnetic transduction biosensors holds promise for multiplexing applications that can greatly improve point-of-care (POC) diagnostics and subsequent medical care.